Isolation, screening and characterization of hydrocarbon degrading bacteria from oil-contaminated soil - Nur Zaida Zahari; Tan; Fera Nony Cleophas; Sahibin Abd Rahim; Rohana Tair; Kamsia Budin; Farrah Anis Fazliatul Adnan (Faculty of Science and Natural Resources, Universiti Malaysia Sabah, 2024)
Petroleum hydrocarbon plays an essential role to human beings as a non-renewable energyproducing resource. The usage of petroleum hydrocarbon will bring environmental issues such as oil contamination in soil and water, which may bring hazardous impacts to human beings. Bioremediation by using treatment of hydrocarbon-degrading bacteria is an alternative method that is cheaper and more environmentally friendly when compared to other traditional methods. In this study, hydrocarbondegrading bacteria are isolated from soil samples in oil-contaminated sites using direct plate technique and streak plate technique. The growth of the isolated bacteria strain added with 5% (v/v) of crude oil in Ramsay broth is then monitored its growth for 24 days with a UV spectrophotometer. The bacteria strain with the highest growth rate (NAY-2) was inoculated in a bioreactor containing three different concentration levels of crude oil-contaminated soil. Besides that, the isolated bacteria strains were also characterized according to their colony morphology, cellular morphology, Gram staining results, and biochemical test. Among the three different concentrations, NAY-2 has reduced the highest total petroleum hydrocarbon concentration in 15% (v/v) concentration level of crude oil contaminated soil with a 5.8% of reduction. When comparing it to bioreactor with natural attenuation treatment, bioreactor with inoculation of NAY-2 showed a significantly higher amount of total petroleum hydrocarbon reduction. Thus, bioremediation with indigenous hydrocarbon-degrading bacteria species will deliver a better result in treating oil-contaminated soil when comparing it to natural attenuation.